Improvement of settlement calculations of building foundations by increasing the reliability of determining soil compressibility indices - Vynnykov, Yuriy; Hajiyev, Muhlis; Aniskin, Aleksej; Miroshnychenko, Irina (Academic journal Industrial Machine Building Civil Engineering, 2019)
Ways to improve the methods of calculating the foundations bases’ settlements by increasing the reliability of determining the soil compressibility indices are substantiated. The complex approach to refinement of the buildings bases' settlements calculation by the layer summation method is investigated by accounting for the soil deformation modulus variability in the full pressure range perceived by the base at loading; soil strength coefficient βZ; soil deformation anisotropy by elastic orthotropic model; tendencies to magnitude variation in the soil deformation modulus in depth of the body under the foundations and within the artificial bases built with the soil compaction. There was also proved the possibility of increasing the accuracy of the predicting method for the buildings' foundations base settling using the soil compression index and accounting for the pressure effect on the soil deformation parameters in depth of the compressible strata.